The Influence of Organizational Culture on Organizational Citizenship Behavior Through Organizational Commitment (Study of Employees at the Mona Plaza Hotel Pekanbaru) - Ambarwati, Ririn; Kasmiruddin; Mandataris (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research was conducted because the author found problems regarding weak organizational citizenship behavior of employees seen from the development of the number of employees who experienced fluctuations and the development of employee absenteeism levels which showed that every year all employees were still found to be absent from work. The purpose of this study was to ascertain and examine how organisational culture affects organisational citizenship behaviour in Mona Plaza Pekanbaru hotel workers through organisational commitment. There were two categories of data that were gathered for this study: primary and secondary data. Respondents filled out surveys in order to provide primary data. The results of the Indirect Effect test indicate that the results are significant for the organisational culture variable on organisational citizenship behaviour through organisational commitment at the Hotel Mona Plaza, Pekanbaru. The results of the Direct Effect test showed that the results were not significant on the organisational culture variable on organisational citizenship behaviour at the Mona Plaza Hotel Pekanbaru. The results of the Significant Results test showed that the results were significant on the Organisational Culture variable on Organisational Commitment at the Mona Plaza Hotel Pekanbaru.